ANALISIS KONTRIBUSI PAJAK DAN RETRIBUSI DAERAH TERHADAP TARGET DAN REALISASI PENDAPATAN ASLI DAERAH (PAD) PROPINSI KALIMANTAN TIMUR TAHUN 2005 SAMPAI TAHUN 2011 - Agus Salim (EKONOMIA, 2013)
Analysis of Contribution of Taxes and Levies agains Target and Actual Revenue (PAD) of East Kalimantan in 2005 until the year 2011 (under the guidance of lecturers Mr Eddy Soegiarto and Mr Imam Nazarudin Latif).This research aims to determine the achievement of local revenue receipt to the set targets and to determine how much the contributions made regional tax and retribution against targets and revenue realization, measurement of both components is considered particularly important given the high contribution should be given to improve PAD to encourage regional economic growth and improve the region's autonomy in financing development.